Modified Dye-Sensitized Solar Cell (Dssc) For Enhancement Of Photovoltaic Properties - Jaafar, Hidayani (2019)
Dye-sensitized solar cells (DSSC) are promising low-cost photovoltaic devices that have a good chance to become a competitor to p-n junction solar cells based technology. DSSCs are fabricated from abundant and cheap materials via inexpensive processes and are likely to be a significant contributor to the future commercial photovoltaic technology. Therefore, by using natural dyes as sensitizers is one of the alternative ways to reduce the fabrication cost of DSSC. However, the efficiency (ɳ) of these natural dyes is still low (<2 %) compared to the existing solar cell technology. Therefore, the aim of this work is to optimize DSSC capability by identifying the most suitable natural dyes to be used as sensitizers and coupled with further improvement through the modification of both photoanode and counter electrode in order to enhance the photovoltaic properties using natural dye. There are four phases in this study. For first phase, E. conferta and G. atroviridis were selected as natural dyes to be used as sensitizers. Efforts are tried to enhance the device performance but at the same time used of low cost sensitizers. E. conferta has been selected due to better photovoltaic properties and produced better ɳ (1.18%) compared to G. atroviridis (0.85%). In second phase, modification of photoanode for enhancement of photovoltaic properties using E. conferta with different amount Nb-doped TiO2 (0–5 wt% of Nb) were synthesized via solid state technique. By doping with 1.0 wt% Nb-doped TiO2, the ɳ increased to 1.40%. In third phase, further modification in counter electrode using carbon black-TiO2 composite was investigated. In this phase, three parameters were varies which are different amount of carbon black, different sintering temperature and different sintering time for carbon black-TiO2 composite counter electrode. DSSC-based on 15 wt% of carbon black-TiO2 composite counter electrode reached the highest ɳ (2.5%) by using E. conferta as sensitizer. Upon modification of sintering parameter at 525 °C for an hour, ɳ increased to 2.77%. Therefore, by using E. conferta as natural sensitizer, ɳ has increased to almost 3% when integrated with modified photoanode (1.0 wt% Nb-doped TiO2) and counter electrode (15 wt% carbon black-TiO2 composite that sintered at 525 °C for an hour).